PENGARUH IMPLEMENTASI PROGRAM PRAKERIN TERHADAP MUTU LULUSAN SMK - Adang Ardali (MADINASIKA, 2020)
The phenomenon of the low quality of SMK graduates is the background of this research. The low quality of graduates is indicated by the fact that there are still aspects of graduate competency standards that have not been fulfilled. The causes include the inadequate implementation of the internship program. The purpose of this study is to determine: a) Implementation of Internship Program; b) Quality of SMK graduates; c) The magnitude of the influence of the implementation of the Prakerin program on the quality of SMK graduates. This study uses a quantitative approach with a survey method to examine a generalized sample. The data collection tool used a questionnaire, the data obtained were analyzed statistically. The design of the analysis is descriptive and subjective. The results showed that descriptively the implementation of the internship program was good, but there were still weaknesses in terms of provide feedback; The quality of graduates is also good, but there are still weaknesses in terms of application of values in life.. Perivikatively, the implementation of the apprenticeship program has a positive and significant effect on the quality of vocational graduates with a magnitude of influence of 40,70%, the remaining 59,30% is influenced by other factors. In conclusion, the implementation of the apprenticeship program has an effect on the quality of SMK graduates.